الاعتراف ودوره في تمتين الهوية التنظيمية في المؤسسة - حميدي, الطيب; عريف, عبدالرزاق (جامعة الوادي - University of Eloued, 2023)
ملخص: تهدف هذه الدراسة الى التعرف على أهم الأبعاد والمتطلبات التي تسهم في بناء وتقوية الهوية التنظيمية في المؤسسة الجزائرية, باعتبار الأخيرة فضاء اجتماعيا ثقافيا, للأفراد الفاعلين، تتم فيه عمليات وعلاقات اجتماعية ثقافية، والتي بوصفها علاقات بين ذوات تبحث عن الاعتراف المتبادل, الذي يعمل على وضع حد للصراعات التنظيمية القائمة على الظلم والسيطرة والهيمنة، ومن ثم تحقق هذه الذوات وجودها وتبني نسيجا اجتماعيا تنظيميا أكثر تماسكاً وانسجاماً. من هذا المنطلق جاءت هذه الورقة البحثية كمحاولة لإسقاط إحدى المقاربات السوسيولوجية المعاصرة (النظرية النقدية الجديدة)، التي تثير مسألة الاعتراف أو بالأحرى الاعتراف المتبادل, وكيف يُكْسِبْ هذا الاعتراف وعي الفرد بذاته؟, أي أن تشكل الهوية الذاتية للأفراد في المجتمع مرهون بشكل من أشكال الاعتراف، والاسقاط في هذا المقام سيكون بين الاعتراف والهوية التنظيمية، وبكيفية تمتينها داخل المؤسسة، وعليه تتمحور إشكالية هذه الورقة البحثية حول التساؤل التالي: ما هو دور الاعتراف بين الفاعلين في تمتين الهوية التنظيمية في المؤسسة؟ . Summary: This study aims to identify the most important dimensions and requirements that contribute to building and strengthening the organizational identity in the Algerian institution, as the latter is a social and cultural space for active individuals in which social and cultural processes and relations take place, which as relationships between persons looking for mutual recognition, which works To put an end to the organizational conflicts based on injustice, domination and domination, and then these selves achieve their existence and build a more coherent and harmonious organizational social fabric. From this point of view, this research paper came as an attempt to drop one of the contemporary sociological approaches (new monetary theory) that raise the issue of recognition, or rather mutual recognition, How does this recognition gain the individual's self-awareness? That is, the formation of the self-identity of individuals in society is contingent on some form of recognition, and the projection in this respect will be between recognition and organizational identity, and how it is strengthened it within the institution. Accordingly, the problematic of this research paper revolves around the following question: What is the role of recognition among the ?actors in strengthening the organizational identity in the institution
مقال
Keywords: الاعتراف- الهوية التنظيمية- تمتين الهوية التنظيمية; recognition - organizational identity - strengthening organizational identity